Emergence and Persistence of Resistance-Associated Substitutions in HCV GT3 Patients Failing Direct-Acting Antivirals - Mushtaq, Saima; Hashmi, Asraf Hussain; Khan, Amjad; Asad Raza Kazmi, Syed Muhammad; Manzoor, Sobia (Frontiers in Pharmacology, 2022)
Background The hepatitis C virus has a high mutation rate, which results in the emergence of resistance-associated substitutions (RASs). Despite direct-acting antivirals' (DAAs) efforts to treat chronically infected HCV genotype 3 (GT3) patients, there are concerns about the emergence and persistence of RASs in DAA failures. The objective of this study was to determine the prevalence of clinically relevant RASs in HCV NS5A and NS5B regions before and after treatment to better understand the role of RASs in treatment failures. Methods Viral RNA was extracted before and after treatment from serum samples. NS5A and NS5B regions of HCV were amplified using Nested PCR followed by Sanger sequencing. The nucleotide sequences were aligned against HCV GT3 reference sequences, and amino acid substitutions were analyzed using the geno2pheno [hcv] web server. Results Seventy-six patients failing DAAs therapy were stratified from the cohort of 1388. RASs were detected at baseline in 15/76 patients and at relapse in 20/76 patients with cirrhosis and previously treated with interferons. The most prevalent NS5A RAS was Y93H found in all treatment-failing patients (14/54 in DCV vs 6/22 in VEL) followed by A62S/T and A30K. No RASs were identified in NS5B. RASs that were present at baseline persisted through the 24-week follow-up period and were enriched with emerging RASs during treatment. The presence of RASs may be one of the causes of treatment failures in 26.3% patients. Amino acid substitutions were present at baseline in most of the patients with RASs against NS5A inhibitors. Patients with baseline Y93H and/or A30K relapse more frequently than patients harboring A62S/T. Conclusion Treatment-failing patients harbored NS5A RASs, the most frequent were A30K (5/20), A62S/T (20/20) and Y93H (20/20). Direct resistance testing is recommended for optimizing re-treatment strategies in treatment-failing patients.